The dreamkeepers successful teachers of African American children - Ladson-Billings, Gloria, 1947- (Jossey-Bass Publishers, 2009)
Gloria Ladson-Billings revisits the eight teachers who were profiled in the first edition and introduces us to new teachers who are current exemplars of good teaching. She shows that culturally relevant teaching is not a matter of race, gender, or teaching style. What matters most is a teacher's efforts to work with the unique strengths a child brings to the classroom. --from publisher description.